Analysis of Arief Muhammad's Organic Electronic Word of Mouth In Promoting Prepp Studio Through Instagram Social Media - Ahmad, Rifqi Nur; Wahyuni, Itca Istia (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study aims to analyze the effectiveness of an electronic word-of-mouth (eWOM) campaign conducted by Prepp Studio, a men's fashion brand in Indonesia, in collaboration with a well-known influencer, Arief Muhammad. The objective is to understand how eWOM, particularly organic word-of-mouth, can be generated and measured through social media platforms like Instagram and online news media. A descriptive qualitative method was employed, guided by a post-positivism paradigm, with data collected through interviews. The findings reveal that the campaign successfully generated organic eWOM, with the Pikiran Rakyat Media Network acting as Talkers by disseminating campaign messages. The primary topic of the campaign was politics, and it utilized tools such as Instagram and online news outlets. Audience participation was encouraged through Instagram Stories and posts, fostering direct engagement. Tracking engagement and feedback were facilitated using online tools, demonstrating the campaign's success in enhancing audience involvement. The study concludes that the campaign effectively leveraged the 5T’s of word-of-mouth marketing—Talkers, Topic, Tools, Taking Part, and Tracking—to create a substantial impact on public discourse. These findings contribute to the theoretical understanding of eWOM strategies in digital marketing and their role in influencing consumer behavior.